Estudo de turbina para implantação em uma central hidrelétrica - Munhoz, Guilherme Pawlak (2015)
In October 2013, The owner of the area where there was the old Steel Plant Marumby Ltda - Usimar in City-Rio Branco do Sul/PR, demonstrated interest in revitalizing the hydroelectric plant located on his property. Having the release of potential hydroelectric use by the Águas Paraná – Instituto das Águas do Paraná, the owner sought a group of students to assess the feasibility of generating energy on the old mill located on the river Rancharia. The presented work deals with the study of water turbines that will be applied in hydropower: Francis, Pelton, Kaplan and Banki. Will be exposed the history of turbines, their functionality objectively and capabilities of power generation based on hydrological data collected in previous studies. This study, while the educational benefit to UTFPR and his students because they can combine theory and practice, will provide the region of Rio Branco do Sul hydroelectric revitalization and development , given that it is completely abandoned and unprofitable. It was found that all the turbines can be used in the implementation of the hydroelectric plant Ranchi. However, the low flow design found possibly be unfeasible to reactivate the plant.